1994
DOI: 10.1017/s0022215100128282
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinusitis in children with otitis media with effusion

Abstract: Sinus radiographs have been carried out on 240 new cases of childhood otitis media with effusion (OME). When the films were suggestive of infection, maxillary sinus washouts were carried out as part of the surgical treatment. Abnormal X-rays were obtained in 28 per cent of the study group, but only 16 cases (seven per cent) of sinus infection were confirmed on antral lavage. In those with positive washouts, there was an apparent relationship between the findings in the maxillary sinuses and middle ears of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…These findings suggest that appropriate antibiotic treatments may be effective in patients with infectious diseases of the sinus and middle ear. Successful treatment of sinus infections was shown to lead to cure of middle ear diseases [13]. Moreover, treatment of uncomplicated acute otitis media and acute bacterial sinusitis with amoxicillin was very effective on OME in the same patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that appropriate antibiotic treatments may be effective in patients with infectious diseases of the sinus and middle ear. Successful treatment of sinus infections was shown to lead to cure of middle ear diseases [13]. Moreover, treatment of uncomplicated acute otitis media and acute bacterial sinusitis with amoxicillin was very effective on OME in the same patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the possibility exists that Eustachian tube dysfunction is caused by adenoid hypertrophy. Mills et al (17) reported that accompanied sinusitis plays an important role in the progression of OME by Eustachian tube dysfunction due to Eustachian tube salphingitis rather than direct bacterial dissemination. Therefore, obviously a simple comparison of bacterial-positive rates cannot definitively conclude a correlation of direct bacterial dissemination into the middle ear cavity by adenoid hypertrophy and sinusitis and OME.…”
Section: Discussionmentioning
confidence: 99%
“…Mills performed sinus radiographs in 240 children with OME and found abnormalities in 28% of cases, though only in 7% an infection was confirmed by a sinus lavage [21]. The same authors argued that radiograph -which currently is no longer considered a reliable diagnostic tool in the diagnosis of sinusitis [4] -may underestimate sinusitis.…”
Section: Discussionmentioning
confidence: 99%